2020
DOI: 10.2298/abs200218018z
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA NEAT1 exacerbates non-small cell lung cancer by upregulating EIF4G2 via miR-582-5p sponging

Abstract: In this study, we aimed to elucidate the role of long non-coding RNA nuclear enriched abundant transcript 1 (lncRNA NEAT1) in non-small cell lung cancer (NSCLC). Quantitative real-time polymerase chain reaction (qRT-PCR) was employed to detect the abundance of NEAT1, microRNA-582-5p (miR-582-5p) and eukaryotic translation initiation factor 4 gamma 2 (EIF4G2). Proliferation, apoptosis, metastasis and glycolytic metabolism were determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…MALAT1 regulated the glucose metabolism of hepatocellular carcinoma cells by enhancing translation of metabolic transcription factor TCF7L2 through mTORC1–4EBP1 axis [ 87 ]. lncRNA NEAT1 represents another example of lncRNAs that contribute to the aggressiveness of non-small cell lung cancer by enhancing eIF4G2 via miR-582-5p sponging effects [ 148 ]. Similarly, lncRNA RP11-284P20.2 enhanced c-met mRNA translation by recruiting eIF3b to c-met and thus promoted proliferation and invasion of hepatocellular carcinoma cells [ 149 ].…”
Section: Acting Mechanisms Of Lncrnas In the Regulation Of Translamentioning
confidence: 99%
See 1 more Smart Citation
“…MALAT1 regulated the glucose metabolism of hepatocellular carcinoma cells by enhancing translation of metabolic transcription factor TCF7L2 through mTORC1–4EBP1 axis [ 87 ]. lncRNA NEAT1 represents another example of lncRNAs that contribute to the aggressiveness of non-small cell lung cancer by enhancing eIF4G2 via miR-582-5p sponging effects [ 148 ]. Similarly, lncRNA RP11-284P20.2 enhanced c-met mRNA translation by recruiting eIF3b to c-met and thus promoted proliferation and invasion of hepatocellular carcinoma cells [ 149 ].…”
Section: Acting Mechanisms Of Lncrnas In the Regulation Of Translamentioning
confidence: 99%
“… The mechanisms of action of lncRNAs on the regulation of cancer-related protein translation [ 31 , 34 , 35 , 38 , 64 , 67 , 68 , 82 , 84 , 85 , 86 , 87 , 148 , 151 , 153 ]. …”
Section: Figurementioning
confidence: 99%
“…Zhao et al concluded that downregulation of Neat1 in NSCLC inhibits its growth, migration, and invasion through the miR-204/NUAK1 axis [ 39 ]. Neat1 was further found to affect NSCLC by elevating its malignant potential via the miR-582-5p/EIF4G2 axis [ 40 ]. As we expected, RBM10 overexpression suppressed Neat1 expression, whereas RBM10 silencing promoted Neat1 expression.…”
Section: Discussionmentioning
confidence: 99%